Manifestações dermatológicas associadas ao tratamento da hepatite C crônica com interferon peguilado, ribavirina e inibidor de protease telaprevir ou boceprevir - Leticia Pires Vaz Brandao Teixeira (2016)
BACKGROUND: The triple therapy of pegylated interferon (PegIFN), ribavirin (RBV) and a protease inhibitor telaprevir (TVR) or boceprevir (BOC) to treat patients with chronic hepatitis C infected with HCV genotype 1 increased the chances of sustained virological response (SRV) but higher rates of adverse events have been reported as compared with double therapy with PegIFN and RBV. The aim of this study was to evaluate the rates and the caracteristics of dermatological adverse events related to triple therapy. METHODS: This prospective and observational study included 39 patients with chronic hepatitis C treated with PegIFN, RBV and TVR (n=29) or BOC (n=10). The prevalence, severity and outcomes related to skin disorders with the triple therapy were compared to double therapy of PegIFN and RBV in a historical control of the same service. RESULTS: 24/39 were men, median age 57 years (51,0-62,0). 29/39 were treated with TVR and 10/39 with BOC, 56,4% were experimented by prior HCV treatment. 76,9% had advanced hepatic fibrosis (Metavir F3 or F4). 24/39 developed rash, mostly (23/24) associated with TVR. 12/39 (30,8%) stopped the triple regimen due to adverse events. Three (7,7%) patients withdraw the protease inhibitor only, while 9 (23,1%) discontinued all drugs. 6/12 (50%) withdraw all drugs because of severity of rash. 6/46 (34,7%) patients presented with rash during dual therapy, but none discontinued the drugs because of dermatological disorders. Triple therapy with TVR was associated with the severity of rash (p < 0.001). In addition, there was an association between the appearance of the rash and the treatment time (p=0.001). Additional dermatological manifestations before and during the triple treatment were xerosis (61.5 % and 87.2 %), dry mouth (20.5% and 70.3%), pruritus (12.8% and 82.1%) and telogen effluvium (10.3% and 48.7%). With dual therapy these values were 52.2% and 95.7%, 9.3% and 79.1%, 8.7% and 47.8%, 4.5% and 65.9%, respectively. CONCLUSIONS: The treatment of chronic hepatitis C with the triple therapy of PegIFN, RBV and TVR is an important cause of rash whose severity can lead to high rates of discontinuation of HCV treatment. This study, conducted by a specialist in dermatology, can alert physicians and patients regarding the occurrence of cutaneous manifestations during treatment of hepatitis C, particularly with schemes including the protease inibitor TVR.